(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article presents information about the place of the Republic of Uzbekistan in the world economy and international relations in the 21st century. The article describes the changing position of Uzbekistan as an owner in the world economy and international relations, the role of import and export, and relations with international organizations. the need- to-know foreign languages in economic relations, how economic words and terms are used are correctly stated.